2019
DOI: 10.1016/j.yhbeh.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Social status in mouse social hierarchies is associated with variation in oxytocin and vasopressin 1a receptor densities

Abstract: Mice living in social hierarchies express different levels of oxytocin receptor (OTR) and vasopressin 1a receptor (V1aR) binding in various brain regions according to their social status.• Alphas and subdominants have higher OTR binding in the nucleus accumbens compared to subordinates.• Alphas have higher OTR binding in the anterior olfactory nucleus compared to subdominants and subordinates.• Alphas have higher OTR and lower V1aR binding in the rostral lateral septum compared to subordinates.• Alphas have lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 99 publications
(129 reference statements)
1
27
3
Order By: Relevance
“…Although this data contrasts with ours, we have to keep in mind that i) the regulation of aggression within the LS, via OXTRs and V1aRs, might be underlined by sex-and speciesdependent mechanisms, as males and females 34 , as well as mice and rats 32,34 , differ in their receptor binding, (ii) we investigated the role of V1aRs, but not V1bRs and differential effects on aggression are likely, and iii) the involvement of endogenous AVP acting on V1bRs has not been shown 56 . Based on our finding that V1aR activation increases sIPSCs frequency exclusively in the dLS, we could hypothesize that V1aR activation might overrule V1bR effects by inhibiting V1bR-responsive interneurons, thereby decreasing aggression.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Although this data contrasts with ours, we have to keep in mind that i) the regulation of aggression within the LS, via OXTRs and V1aRs, might be underlined by sex-and speciesdependent mechanisms, as males and females 34 , as well as mice and rats 32,34 , differ in their receptor binding, (ii) we investigated the role of V1aRs, but not V1bRs and differential effects on aggression are likely, and iii) the involvement of endogenous AVP acting on V1bRs has not been shown 56 . Based on our finding that V1aR activation increases sIPSCs frequency exclusively in the dLS, we could hypothesize that V1aR activation might overrule V1bR effects by inhibiting V1bR-responsive interneurons, thereby decreasing aggression.…”
Section: Discussioncontrasting
confidence: 92%
“…In agreement, high aggression displayed by dominant males has also been linked to reduced septal AVP signaling, i.e. alpha male mice showed decreased V1aR binding in the LS, when compared to subordinate males 32 , and synthetic AVP was able to flatten dominant behavior in rhesus macaques 58 . In lactating females, the link between AVP and aggression seems to be complex as well.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Hierarchical rank has extensive effects on physical and mental health [3][4][5] and therefore could become maladaptive due to the risk factors associated with living in a particular rank. Previous research has shown extensive effects of rank on behaviour, including reproductive success [6], anxiety [7] (but see [8]), social motivation [9] and social contact [10], as well as on gene expression [7] and receptor expression [11].…”
Section: Introductionmentioning
confidence: 99%
“…S6. for the David's score of each individual in the study) as previously described in Lee et al 23,85,86 . Based on David's scores (on group housing Day 6), we selected two urine donors per cohort (alpha = the highest David's score in the group, the most subordinate = the lowest David's score).…”
Section: Group Dominance Structure Emergence Of Hierarchies and Indimentioning
confidence: 99%